Efficacy of corticosteroids on postoperative pain levels after nonsurgical endodontic treatment: An overview of systematic reviews - Serena Lalfakawmi; Alpa Gupta; Seema Bukhari; Dax Abraham; Arundeep Singh; Mrinalini (Saudi Endodontic Journal)
Introduction: According to previously published data, the severity of pain caused by pulp therapy and root canal treatment is more compared to other dental operative procedures. Corticosteroids are one of the most common drugs used in endodontics for reducing postoperative pain levels. The aim of this study is to compare and assess the effect of corticosteroids on postoperative pain levels with an active or passive placebo after nonsurgical endodontic treatment. Materials and Methods: The standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses Checklist was used for framing the review protocol and it was then registered in the International Prospective Register of Systematic Reviews (PROSPERO) database (CRD42022372527). In this overview, systematic reviews with or without meta-analysis that evaluated the efficacy of corticosteroids alone, irrespective of their route, time, dosage of administration, and tooth vitality, in controlling postoperative pain levels in teeth requiring root canal treatment were included. The assessment of multiple systematic reviews tool was used to investigate the methodological quality of the systematic reviews included in this review. Results: The majority of the studies that were selected for this review showed that using corticosteroids led to a significant decrease in pain levels following endodontic treatment, especially at 6 h after completion of treatment. Pain levels were reduced considerably when prednisolone was compared with other forms of corticosteroids. It is suggested that when prednisolone is administered 30 min before the commencement of root canal therapy, it is similar in its effect to using similar doses for a longer duration. However, further randomized controlled trials are required keeping the strict inclusion criteria in mind. Conclusions: The systematic reviews summarized in this overview support the conclusion that using corticosteroids greatly reduced postoperative pain following endodontic treatment, and they also dispel any misconceptions about corticosteroids’ routine use in moderation.